How Did the War and Hate in Bosnia-Herzegovina Come into Existence?
Portrait of Serb psychiatrist Jovan Raskovic, who claims responsibility for planting seeds of hatred, nationalism and using group psychology to manipulate the entire Serb nation into starting the war.